Sequential Nitrification/Mixotrophic Denitrification Process in Single Bioreactor: Performance and Microbiology of Two Types of Sequencing Batch Bioreactors - Pages-Diaz, J (ELSEVIER SCI LTD, 2025)
The integration of sequential nitrification/mixotrophic denitrification (SNMD) in a single bioreactor is rarely reported. This study adapted an industrial inoculum to SNMD in a single bioreactor configuration, comparing a conventional sequencing batch reactor (SBR) and a zeolite-carrier SBR (SBBR) over 276 days across three phases: sequential nitrification heterotrophic denitrification (SNHD) adaptation, increased TAN loading, and SNMD with sulfide (HS--S) addition. Under SNHD conditions, both systems achieved > 99 % TAN removal with complete NO3--N reduction. After HS--S addition, NO2--N accumulated, yet denitrification recovered after 90 days. Under SNMD, TAN removal averaged 93.4 +/- 5.6 % in the SBR and 90.0 +/- 10.6 % in the SBBR (p > 0.05). While performance remained similar, zeolite influenced microbial community composition, particularly under sulfur-driven conditions. Therefore, the SNMD process was successfully developed in a single reactor, with or without zeolite, which only affected microbial abundance.